Vitamin K Dependent Proteins in Fetal Hemostasis at Mid Trimester of Pregnancy - Forestier, F; Daffos, F; Rainaut, M; Solé, Y; Amiral, J (Thrombosis and Haemostasis, 1985)
The vitamin K dependent coagulation factor activities were measured in 63 normal human fetuses from 19 to 28 weeks of pregnancy. These activities were included between 9 to 28 percent of normal adult levels.Prothrombin antigen, factor IX antigen and protein C were also measured. There is a good correlation between prothrombin procoagulant activity and antigenicity, suggesting that low level of these vitamin K dependent proteins in fetuses is probably a consequence of liver immaturity.
Keywords: Haemostasis; Fetus; Vitamin K